Dual infection in pregnancy: Disseminated Mycoplasma hominis and necrotizing herpes simplex 2 hepatitis. (June 2018) - Sonpar, A.; Brown, K.; Chen, J.; Megran, D.; Sabo, M.; Cervera, C.; Girgis, S.; Kabbani, D.
Highlights: We describe an interesting case of a pregnant woman with simultaneous necrotizing HSV hepatitis and disseminated M. hominis infection. Mycoplasma hominis is part of the genitourinary flora in sexually active people and can cause disseminated infection in immunocompromised patients. Detection of Mycoplasma spp. in the laboratory is difficult due to their fastidious growth requirements. Detection of M. hominis and antimicrobial susceptibility testing of this fastidious organism in the clinical laboratory is discussed. M. hominis systemic infection should be considered in pregnancy when initial cultures are negative and there is no response to standard empiric antimicrobial therapy. Abstract: Mycoplasma hominis is part of the genitourinary flora in sexually active people and can cause disseminated infection in immunocompromised patients. We describe a rare case of an immunocompetent pregnant woman with simultaneous necrotizing HSV hepatitis and disseminated M. hominis infection. Detection of M. hominis and antimicrobial susceptibility testing of this fastidious organism in the clinical laboratory is discussed.